Aplikasi Biopsikososial-Spiritual untuk Bekas Penagih Dadah bagi Mengelakkan Relapse: Perbincangan Kumpulan Fokus: Application of the Biopsychosocial-Spiritual Approach for Former Drug Addicts to Prevent Relapse: A Focus Group Discussion - Sa`ari, Che Zarrina; Syed Muhsin, Sharifah Basirah; Zainal Abidin, Mohd Syukri; Abd Rashid, Rusdi; Chik, Hasimah; Haji Yahya, Hajah Masuriyati (Jurnal Usuluddin, 2025)
Drug addiction is a global issue that continues to have significant impacts on individuals, families, and communities. One of the main challenges in the recovery process is the risk of relapse, which refers to the recurrence of addictive behaviour. This article discusses the application of the biopsychosocial-spiritual approach from an Islamic perspective as a holistic effort to help former drug addicts prevent relapse. This study employs a qualitative method through a Focus Group Discussion (FGD) involving nine experts from various fields, including Sufism, Islamic Psychotherapy, Islamic Psychology, psychiatry, drug rehabilitation, as well as social and community work. The findings were analysed using thematic analysis, resulting in several key themes based on four components: biological or physical, psychological, social, and spiritual. Essential elements such as medical treatment (e.g., Methadone), psychospiritual therapy, reinforcement of religious values, social skills, and community support were identified as core components in the development of an intervention module. This study recommends that the Islamic Psychospiritual approach be used as the foundation for a comprehensive and practical rehabilitation module to strengthen self-resilience and reduce the risk of relapse among former drug addicts.